Design and Performance Analysis of a Solar Air (SA) Heater with Phase Change Material (PCM) Heat Storage for Residential Applications (International Journal of Innovative Research in Engineering & Management, 2023)
Outlet air temperature can be seen as one  of the main determinants of the functioning of the solar air  heaters and this is one of the main features of the PCM.  Variations in solar radiation can be considered a key  determinant of the functioning of solar air heaters used in  residential applications. Weather conditions can influence  the presentation of the air heaters operated by solar energy  to agreat extent. Structuring of collector plates needs to be  done in an effective manner by designers of air heaters used  in residential applications. The contact surface of the  collector plates is the other determinant of the presentation  of the air heaters. A blower is one of the most vital  components used in air heaters and the efficiency of the  blower can improve the execution of this device. Transport  fluid has been identified as a vital factor that can have a  huge impact on the functioning of air heaters operated by  solar energy. Air thermal capacity can be considered as the  other determinant of the functioning of this device. The  high cost of fluid circulation has been found as one of the  negative factors in the structure and functioning of the air  heaters used in residential applications.
Keywords: Solar air heaters; Phase change materials; Environmental factors; Thermal capacity; Solar energy